Nanoarchitectonics for Brain Drug Delivery - Singh A.K.; Chaturvedi V.K.; Singh J. (My University, 2025)
This book discusses basics of brain diseases and the role of nanobiotechnology in existing treatment options for neurodegenerative disorders. It begins with an overview of brain diseases and the need for novel drug-delivery approaches. It highlights the current route for the intranasal advanced drug-delivery systems for brain diseases. It also discusses innovative categories of drug-delivery systems, including mesoporous silica nanoparticles, polymeric nanocarriers, and lipid-based nanocarriers through multi-responsive DDSs and their implications in brain disorders. Features: Includes an overview of brain diseases and highlights the need for novel drug-delivery approaches Focuses on theoretical aspects of advanced drug-delivery systems for brain diseases including challenges and progress in nose-to-brain delivery Provides an overview of technological approaches and their implications for neurodegenerative disorders, central nervous system (CNS), and brain drug delivery in brain cancer Discusses key advances in the development of polymer nanoparticles for drug delivery to the CNS Reviews the role of herbal medicines and naturally derived polymeric nanoparticle for the treatment of neurodegenerative disorders This book is aimed at graduate students and researchers in biomedical engineering, biotechnology, drug delivery, and neurology. © 2024 selection and editorial matter, Anurag Kumar Singh, Vivek K. Chaturvedi, and Jay Singh; individual chapters, the contributors.